The Aged Lower Urinary Tract: Deficits in Neural Control Mechanisms - Hardy, Cara C. (Frontiers in Aging, 2021)
Bothersome urinary symptoms plague many older adults and disproportionally affect women. Under reporting of symptoms and general stigma / embarrassment associated with incontinence has negatively impacted the availability of treatments, as research cannot be championed if the severity of the problem isn’t apparent. Available therapeutics have limited efficacy and are often not recommended in aged patients. Lower urinary tract function has a long and rich history in animal studies; while much of the underlying anatomy has been described, including neural control mechanisms, the impact of aging has only just begun to be addressed. Recent work has provided strong evidence that neural control over micturition is significantly impacted by aging processes. This mini review discusses recent findings regarding how aging impacts the neural control mechanisms of micturition.